Students’ construction of projection concepts through independent exploration in a technology-enhanced learning environment - Aris Hadiyan Wijaksana; Yaya Sukjaya Kusumah; Turmudi Turmudi (Universitas Hamzanwadi, 2026)
Conventional descriptive geometry instruction often fails to facilitate accurate spatial visualization, perpetuating epistemological obstacles. This study investigates how integrating independent exploration via GeoGebra impacts students' knowledge construction of orthogonal projection concepts. A descriptive qualitative case study was conducted involving 16 mathematics education students at the State University of Jakarta during the odd semester of 2026. Data were collected using a conceptual understanding test comprising three hierarchical questions and a structured interview guide, and then analyzed through an interactive qualitative model. Findings indicate that GeoGebra functions beyond a mere visual aid; it acts as a cognitive instrument mediating instrumental genesis. Specifically, independent exploration utilizing dragging and 3D manipulation empowered students to diagnose and dismantle persistent epistemological obstacles related to dimensional transformations and planar intersections. However, varying levels of student dependence on instructor scaffolding highlight that successful instrument adaptation relies on individual learning dispositions. The study implies that effectively integrating technology in geometry education requires a differentiated pedagogical approach and a shift toward orchestrated digital exploration.